Dating the Noceto Vasca Votiva, a unique wooden structure of the 15th century BCE, and the timing of a major societal change in the Bronze Age of northern Italy - Cremaschi, Mauro; Griggs, Carol; Kocik, Cynthia; Mutti, Angela; Zerboni, Andrea; Manning, Sturt W. (PLOS ONE, 2021)
The Noceto ‘Vasca Votiva’ (votive tank), discovered in excavations on a terrace at the southern edge of the Po Plain, northern Italy, is a unique well-preserved wooden (primarily oak) structure dated to the advanced through late Middle Bronze Age ( 1600–1300 BCE). This complex monument, comprising two super-imposed tanks, is generally linked with an important but uncertain ritual role involving water. The context provides extraordinary preservation of both wooden, other organic, and cultural finds. The key question until now, hindering further interpretation of this remarkable structure, has been the precise date of the tanks. Initial work pointed to use of the two tanks over about a century. Using dendrochronology and radiocarbon ‘wiggle-matching’ we report near-absolute construction dates for both of the tanks. The lower (older) tank is dated 1444±4 BCE and the upper (more recent) tank is dated 12 years later at 1432±4 BCE. This dating of the construction of the Noceto tanks in the 3rd quarter of the 15th century BCE further enables us to reassess the overall period of activity of this wooden complex and its association with a major period of societal change in the Bronze Age of northern Italy starting in the later 15th century BCE.